2017
DOI: 10.1093/europace/eux063
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of elevated high-sensitivity cardiac troponin T in patients admitted to an emergency department with atrial fibrillation

Abstract: http://www.clinicaltrials.gov; Unique identifier: NCT02542189.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…* Medical record software not in use from 11 November 2011 to 9 December 2011 AF denotes atrial fibrillation, hsTnT high-sensitivity troponin T. (Reproduced with permission from Oxford University Press [18]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…* Medical record software not in use from 11 November 2011 to 9 December 2011 AF denotes atrial fibrillation, hsTnT high-sensitivity troponin T. (Reproduced with permission from Oxford University Press [18]).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, novel risk scores for patients with AF using biomarkers have been derived from RCT populations [1517]. In the setting of an emergency department, we have shown, that elevated cardiac troponin levels are associated with higher mortality in patients with AF [18].…”
Section: Introductionmentioning
confidence: 99%
“…Explanatory factors were selected by examining the multicollinearity among the variables using stepwise regression; four factors (CHADS 2 score, whole blood passage time, d-ROMs test, and hs-cTnT level) were identified as independent variables. Figure 3 shows the receiver-operating characteristic curve analysis for the detection of high CHADS 2 scores (≥ 2) and elevated hs-cTnT levels (> 0.014 ng/mL), based on previous studies [22, 23]. The maximum Youden’s index indicated that the optimal cutoff values of skin autofluorescence to determine high CHADS 2 scores and elevated hs-cTnT levels were 2.6 AU and 2.7 AU, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Recent clinical studies have shown the clinical importance of hs-cTnT levels as a prognostic factor in patients with atrial fibrillation [23, 33]. In addition, hs-cTnT is used as a biomarker to clinically evaluate the severity of myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponins are widely available in primary care and in hospitalised patients, provide plausible biological information on underlying pathophysiology, are established in the diagnosis of ACS, 1 improve risk assessment in ACS, 18 atrial fibrillation 19 and pulmonary embolism 20 and may guide therapeutic management in several acute and chronic diseases. It is tempting to speculate that a single biomarker-based risk prediction tool may be better adopted for prognostication than a complex multivariate score.…”
Section: Introductionmentioning
confidence: 99%